(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
An essential component of human resource management in business is assessing employees’ performance, which refers to a person’s ability to perform their duties effectively. Companies assess their employee’s performance annually or quarterly to identify areas for improvement and encourage success. However, the process of assessing a worker’s performance is complicated and requires careful planning, execution, and evaluation. This utilized a descriptive research method, which employed twenty-five (25) employees of AAA Ang Plus manufacturing; it also used a survey questionnaire to gather data to have a basis for this study. The result reveals that the Assessment of employees’ performance of AAA Ang plus manufacturing, in terms of quality of work, quantity of work, employee relationship, job knowledge, and punctuality, is good, and the employees are satisfied, but still, there are some areas that need to be developed. The problems encountered by the assessment of team leaders manager on employee’s performance, it turned out that the three biggest problems encountered were lack of knowledge of many managers and supervisors – lack of the necessary knowledge and skills to conduct effective employee assessments; lack of preparation – inadequate preparation by both managers and employees can lead to incomplete or inaccurate assessments; poor employee discussion communication between managers and employees during the assessment process can hinder the understanding of expectations and goals This study recommended that manufacturing should provide comprehensive training and development programs for managers and supervisors. These programs should focus on enhancing their understanding of assessment techniques, providing feedback, and setting realistic goals. Encourage regular and open dialogue between managers and employees. Implement a structured system for continuous feedback and performance discussions throughout the year. This allows for timely identification of challenges and areas for improvement. Managers should actively listen, provide constructive feedback, and collaborate with employees to set meaningful goals. Standardized assessment terminology within the organization to ensure clarity and consistency.